Flush, Pottawatomie County - Dunham, Tim (Kansas State University, The Chapman Center for Rural Studies, 2011)
This paper explores the effects of transportation on the community of Flush, Pottawatomie, County, Kansas from 1854 to 1914. The paper will demonstrate how transportation was related to the rise and fall of Flush. It utilizes books, interviews, Platt maps, and websites.
Tim Dunham, “Flush, Pottawatomie County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/30.
Keywords: Dekat; Pottawatomie Indian Trail; Reverend Biehler; St. Mary's Indian Mission; Vermillion River; Pottawatomie County